Analisis Improvisasi Tenor Saxophone Chris Potter pada Karya “Wistful” - Purba, Bernard Zulfredo; Sanjaya, Singgih; Prasetyo, Agoeng (Institut Seni Indonesia Denpasar, 2025)
Purpose: This article discusses the analysis of Chris Potter's improvisation on the song Wistful. The author chose Chris Potter because he is an inspiration in playing jazz, because of his very high skills (virtuoso). The song Wistful was released on an album entitled